Comparison of Roll and Pitch Among Patients with Vertical and Horizontal Skeletal Patterns Using Cant-O-Meter: A New Gyroscopic Device for Measuring Occlusal Cant. Issue 2 (April 2022) - Ravi, Janani; Jnaneshwar, Poornima; Krishnaraj, R.; Ravi, K.
In Orthodontics, initial classification of malocclusions was based on planar malocclusions in the anteroposterior, transverse and vertical planes that were based only on translation of the jaws in space. In 2007, Ackermann and Proffit introduced rotational components—roll, pitch, and yaw—analogous to the position of the airplane in space. These rotations can result in canting of the occlusal plane. There are no quantitative methods available in the literature for a precise estimation of the occlusal cant. Qualitative evaluation of occlusal cant is subjective and is associated with inter-individual variations. This article describes an indigenously devised simple chairside device that can quantify cant of the occlusal plane in terms of the roll and pitch in degrees. There is accurate quantification of cant, which can be used effectively in many clinical scenarios.